The predictive value of the triglyceride glucose index combined with cystatin C for the prognosis of patients with acute coronary syndrome - Wang, Chen; Liao, Pinliang; Tang, Chuanqin; Chen, Chunlin; Zhang, Xiaoyu (Frontiers in Endocrinology, 2024)
Background: Recent studies have shown that the triglyceride glucose index (TyG) and cystatin C (CysC) are closely related to cardiovascular disease, but there is limited research on the prognosis of patients who with acute coronary syndrome (ACS) after percutaneous coronary intervention (PCI). The aim of this study is to explore the predictive value of the combination of TyG index and CysC in predicting major adverse cardiovascular events (MACEs) in ACS patients who underwent PCI. Methods: This retrospective study included 319 ACS patients who underwent PCI. The clinical endpoint is the occurrence of MACEs, including all-cause mortality, heart failure, non-fatal myocardial infarction, target vessel revascularization, and angina requiring hospitalization. Patients were classified into MACEs group (65 cases) and non-MACEs group (254 cases). Univariate factor and multivariate analysis were used to identify predictors of MACEs. Receiver operating curve (ROC curve) of prediction model of MACEs were drew. Additionally, the net reclassification improvement (NRI) and integrated discrimination improvement (IDI) index were calculated to further assess the additional predictive value of the risk factors for MACEs. Subgroup and interaction analysis between the TyG index and CysC with MACEs were draw in various subgroups. Patients were stratified according to the optimal cutoff point value of the TyG index and the CysC determined by ROC curve analysis. The Kaplan Meier analysis method was used to construct a survival curve one year after PCI. Results: During a median follow-up period of 14 months, 65 (20.38%) patients had experienced at least one primary end-point event. Multivariate logistic regression analysis indicated the TyG index and the CysC were independently associated with the increased risk of MACEs after PCI（OR, 2.513; 95% CI 1.451–4.351; P= 0.001, OR, 4.741; 95% CI 1.344–16.731; P=0.016，respectively）. The addition of the TyG index and the CysC to the baseline risk model had the strongest incremental effect for predicting MACEs in terms of the C-statistic from 0.789 (95% CI 0.723-0.855, P<0.001) to 0.799 (95% CI 0.733-0.865, P＜0.001). Furthermore, Kaplan–Meier analysis demonstrated the TyG index greater than 9.325, and the CysC greater than 1.065mg/ml were significantly associated with an increased risk of MACEs (log‐rank, all P < 0.01).